2007
DOI: 10.4161/cc.6.10.4182
|View full text |Cite
|
Sign up to set email alerts
|

Localized Treatment with a Novel FDA-Approved Proteasome Inhibitor Blocks the Degradation of Dystrophin and Dystrophin-Associated Proteins in mdx Mice

Abstract: Previously published online as a Cell Cycle E-publication: http://www.landesbioscience.com/journals/cc/abstract.php?id=4182 KEy wordS ABStrACtDuchenne Muscular Dystrophy (DMD) is an incurable inherited disease of childhood, characterized by progressive muscle degeneration and weakness. Our previous findings supported the idea that dystrophin and associated proteins, absent or greatly reduced in DMD, are degraded in dystrophin-deficient muscle by the proteasomal-dependent pathway. Indeed, treatment with the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
1
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 32 publications
7
62
1
4
Order By: Relevance
“…Immunohistochemical (Figure 6i) and WB (Figure 6j) analysis confirmed that β-sarcoglycan expression was markedly reduced at the sarcolemma of skeletal muscle fibers from untreated mdx mice, and it was upregulated in muscles of ONX-0914 treated mice. Similar to previously observations by Bonuccelli,6,23 we suggested that dystrophin re-expression allowed the rescue of DGC complex at the sarcolemma. ONX-0914 treatment reduces dystrophic muscle inflammation in 6-weeks-old mice As the fibroadipogenic degeneration of muscular fibers could be promoted by interaction of inflammatory cells with resident muscle cells, 25,26 we analyzed inflammatory infiltrates in ONX-0914 treated skeletal dystrophic muscles.…”
Section: I-proteosome Inhibition Ameliorates Muscular Dystrophic Featsupporting
confidence: 79%
See 1 more Smart Citation
“…Immunohistochemical (Figure 6i) and WB (Figure 6j) analysis confirmed that β-sarcoglycan expression was markedly reduced at the sarcolemma of skeletal muscle fibers from untreated mdx mice, and it was upregulated in muscles of ONX-0914 treated mice. Similar to previously observations by Bonuccelli,6,23 we suggested that dystrophin re-expression allowed the rescue of DGC complex at the sarcolemma. ONX-0914 treatment reduces dystrophic muscle inflammation in 6-weeks-old mice As the fibroadipogenic degeneration of muscular fibers could be promoted by interaction of inflammatory cells with resident muscle cells, 25,26 we analyzed inflammatory infiltrates in ONX-0914 treated skeletal dystrophic muscles.…”
Section: I-proteosome Inhibition Ameliorates Muscular Dystrophic Featsupporting
confidence: 79%
“…Moreover, WB analysis confirmed the expression of a 120 kDa molecular weight dystrophin protein (Figure 6f), accordingly to previous works. 6,23,24 Interestingly, the ONX-0914 treated mdx showed a reduction of the serum creatine phospho-kinases (CPK) released from damaged myofibers, suggesting muscle preservation in treated animals. Serum CPK levels dramatically decreased throughout the treatment, reaching the physiological level observed in wildtype C57Bl mice (Figure 6g).…”
Section: I-proteosome Inhibition Ameliorates Muscular Dystrophic Featmentioning
confidence: 99%
“…Each of the tested proteasome inhibitors restored mutant dystrophin to WT levels at concentrations less than 10 μM. Several previous studies have tested proteasome inhibition to treat the nonsense mutation mdx mouse model of dystrophinopathy (44)(45)(46)(47) but have reported contradictory results. Although proteasome inhibition by MG132 in the mdx mouse restored the amino-terminal fragment of dystrophin translated up to the premature stop codon (44), prolonged treatment with MG132 resulted in no improvement of muscle function (46).…”
Section: Discussionmentioning
confidence: 99%
“…mg/m 2 no segundo ciclo e, no terceiro para 1,60 mg/m 2 . Esse ajuste de dose se justifica pela inibição da atividade do proteassoma pelo bortezomibe ser dose-dependente e de atuação reversível sobre o sitio quimiotripsina-símile, com melhores resultados sobre a fibra muscular quando utilizado na dose máxima (BONUCCELLI et al, 2003;BONUCCELLI et al, 2007).…”
Section: Delineamento Experimentalunclassified
“…No entanto, para diagnostico da deficiência especifica de distrofina no músculo, ambas as técnicas são consideradas efetivas (VAINZOF et al, 1991 Nos estudos de Bonuccelli et al (2003), Assereto et al (2006) e Bonuccelli (2007 melhores resultados quanto restauração da distrofina e proteínas associadas nas fibras musculares tratadas com inibidores de proteassoma ocorreu de forma dose-dependente, ou seja, melhores alterações na integridade da fibra muscular quando administradas maiores doses do inibidor. Em nosso estudo, apesar de termos aumentado a dose a cada ciclo de administração, essa comparação não foi possível, uma vez que realizamos duas biópsias musculares, uma antes do tratamento e após o mesmo (T1).…”
Section: Microscopia Eletrônica De Transmissão (Met)unclassified